Crystal structure of isopenicillin N synthase is the first from a new structural family of enzymes. - Roach, P; Clifton, I; Fülöp, V; Harlos, K; Barton, G; Hajdu, J; Andersson, I; Schofield, C; Baldwin, J (1995)
Penicillin antibiotics are all produced from fermentation-derived penicillins because their chemical synthesis is not commercially viable. The key step in penicillin biosynthesis, in which both the beta-lactam and thiazolidine rings of the nucleus are created, is mediated by isopenicillin N synthase (IPNS), which binds ferrous iron and uses dioxygen as a cosubstrate. In a unique enzymatic step, with no chemical precedent, IPNS catalyses the transfer of four hydrogen atoms from its tripeptide substrate to dioxygen forming, in a single reaction, the complete bicyclic nucleus of the penicillins. We now report the structure of IPNS complexed with manganese, which reveals the active site is unusually buried within a 'jelly-roll' motif and lined by hydrophobic residues, and suggest how this structure permits the process of penicillin formation. Sequence analyses indicate IPNS, 1-aminocyclopropane-1-carboxylic acid oxidase and many of the 2-oxo-acid-dependent oxygenases contain a conserved jelly-roll motif, forming a new structural family of enzymes.